Efektivitas Modul Ajar Pendekatan Kurikulum Cinta dan Tingkat Keaktifan Siswa terhadap Peningkatan Hasil Belajar Matematika Siswa MI - Irma Rosyidah; Siti Lailiyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2026)
This study aims to test the effectiveness of the Love Curriculum Approach Teaching Module and the level of student activity on the mathematics learning outcomes of elementary school students. The research method uses a quantitative approach with a quasi-experimental design and a sample of 32 students. The results of the study show that. Data analysis was carried out using Two-Way ANOVA, which showed that the use of the Love Curriculum Mathematics Teaching Module had a significant effect on mathematics learning outcomes (p < 0.001) and that the level of student activity had a significant effect (p < 0.001). The interaction between the two variables was also significant (p < 0.001), confirming that the module is more effective when used by students with high activity levels. The results of the Tukey HSD follow-up test showed that all group comparisons were significantly different, including the difference in values ​​between the Love Curriculum group having low activity and without the Module having low activity of 10,929 (p < 0.001), as well as the difference between the Love Curriculum group having high activity and without the Module having high activity of 11,833 (p < 0.001). Overall, this study proves that the combination of the Love Curriculum module and student activity contributes significantly to improving mathematics learning outcomes.